AB1470-HPR Beliefs and satisfaction with golimumab as second anti tnf-alpha of patients with spondyloarthritis. go-beyond. (12th June 2018) - Juanola, X; González Fernández, C.M.; García-Carazo, S.; Rodríguez-Hereida, J.; Bachiller-Corral, J.; Martín López, M.; Retuerto Guerrero, M.; Martín Santos, J.; Álvarez-Rivas, N.; Egües Dubuc, C.; Villa-Blanco, I.; Laiz, A.; et al.
Abstract : Objectives: In patients with spondyloarthritis (SpA: axial SpA or psoriatic arthritis [PsA]), treated with golimumab as second biological therapy (after failure or withdrawal of a first anti TNF-α drug), we describe patients' insights with regard to their beliefs and their satisfaction with golimumab therapy. Methods: Patients on golimumab from GO-BEYOND, a retrospective study undergone in 20 Spanish rheumatology clinics, were requested to respond to the Beliefs About Medicines Questionnaire (BMQ). Statements of the BMQ include a 5-item necessity and a 5-item concern scale with Likert response options from "strongly agree" to "strongly disagree". Patients also responded to questions on their satisfaction and experience with golimumab self-injection. Descriptive data are displayed, and responses to the BMQ in axial SpA vs PsA patients were compared with the chi-square test. Results: 123 patients on golimumab as second anti TNF-α responded (81 axial SpA and 42 PsA, mean age 49 years [SD=11], 40% women). Patients showed strong beliefs in the necessity of golimumab for the treatment of their SpA (percentages of "agree" or "strongly agree" to the necessity statements: 50%–80%), but also concerns: half the patients agreed/strongly agreed to be worried about long term effects of golimumab, and ≈30% about becoming too dependent on the drug (table 1). Responses were similar in axial SpA and PsA patients (table 1). 111 patients declared to self-inject golimumab. Of these, 22.7% considered the experience with self-injection as very positive, 66.4% as positive, 10.0% neutral and only 0.9% unfavourable, and the use of the device very easy (37.3%), easy (57.3%), neutral (3.6%) and only 1.8% difficult. Finally 36.4% and 49.1% were very satisfied or satisfied with the interval of administration of golimumab, 11.8% were neutral and only 1.8% and 0.9% declared to be dissatisfied or very dissatisfied. Conclusions: Patients with SpA currently using golimumab as second anti TNF-alpha describe strong beliefs in the necessity of golimumab and good experience and satisfaction with self-administration. The BMQ also identified concerns that should be addressed in the clinic. The study is limited to the subset of patients still on golimumab at the study visit. Acknowledgements: Funded by Merck Sharp and Dohme, Spain Disclosure of Interest: None declared